2012
DOI: 10.1590/s0001-37652012005000036
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in Plasmodium-Red Blood Cells interactions and in cytoadherence

Abstract: Malaria is responsible for more than 1.5 million deaths each year, especially among children (Snow et al. 2005). Despite of the severity of malaria situation and great effort to the development of new drug targets (Yuan et al. 2011) there is still a relative low investment toward antimalarial drugs. Briefly there are targets classes of antimalarial drugs currently being tested including: kinases, proteases, ion channel of GPCR, nuclear receptor, among others (Gamo et al. 2010). Here we review malaria signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 158 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…[57] Finally, ATP is involved in endothelial cell inflammation induced following infection with Plasmodium. [58] Like oxidative stress, RBC infection by P. falciparum induces increased permeability of anions and organic osmolytes. Induction of osmolyte permeability in iRBCs involves autocrine purino-receptor signaling, as extracellular ATP does not induce permeability in uninfected or unoxidized RBCs.…”
Section: Role Of New Permeation Pathways -Nppmentioning
confidence: 99%
“…[57] Finally, ATP is involved in endothelial cell inflammation induced following infection with Plasmodium. [58] Like oxidative stress, RBC infection by P. falciparum induces increased permeability of anions and organic osmolytes. Induction of osmolyte permeability in iRBCs involves autocrine purino-receptor signaling, as extracellular ATP does not induce permeability in uninfected or unoxidized RBCs.…”
Section: Role Of New Permeation Pathways -Nppmentioning
confidence: 99%
“…Although this machinery is not thought to exist in Plasmodium parasites, an analogous system may have evolved to detect this important host protein. Signal transduction regulation inside Plasmodium has been shown as a major mechanism to control parasite development [ 15 ]. In the mammalian host, studies have shown that TNF induces extensive alterations in host microvascular endothelium, including morphological re-organization [ 46 ], release of membrane microparticles [ 47 ], production of other pro-inflammatory cytokines, up-regulation of receptors and apoptosis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these belong to the host responses to parasite infection, whereas there are only limited numbers of studies about signalling events in parasites themselves, despite the existence of an extensive kinase gene family. For example, signal transduction inside Plasmodium has been shown to be a major mechanism to control parasite development [ 15 ] with regulation in P. falciparum by calcium-dependent protein kinase 7 (PfCDPK7) being reported [ 16 ]. PfCDPK1 has been identified as a Ca 2+ -dependent effector that plays a role in microneme secretion during erythrocyte invasion [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these receptors can be exploited as targets so as to design inhibitors of parasite invasion process (68, 69). ATP is also thought to be involved in the host-induced inflammation following the malaria infection (70). …”
Section: Cyclic Nucleotide-based Signaling During Malariamentioning
confidence: 99%